Integrated calcareous plankton biostratigraphy of selected Miocene successions in the Northern Calabria (Italy) - RAO A; GUIDO A; MASTANDREA A; PERRI E; ROMANO C; RUSSO, Francesco; DI STEFANO, Enrico (2006)
An integrated calcareous plankton biostratigraphic approach on six sections cropping out in Northern Calabria allowed to define a revised chronostratigraphic framework for Tortonian-Messinian deposits. Four sections have been investigated in the Amantea Basin (Timpone Napoli, Vallone Salina, Case Vespano, and Cozzo Salice) and two in the Rossano Basin (Vallone Casino and Cozzo Sant'Isidoro). Biostratigraphic analyses have been based on quantitative counting of planktonic foraminifers and semiquantitative counting of nannofossils. The Timpone Napoli and Vallone Salina sections are Late Tortonian in age and referable to the Globorotalia suterae Zone. In terms of nannofossils zonal scheme these sections fall within the Coccolithus pelagicus - Amaurolithus primus Zones. The Case Vespano and Cozzo Salice sections can be ascribed to the Messinian. The Case Vespano section is wholly characterized by the common occurrence of Globorotalia miotumida group. The co-occurrence of Amarolithus delicatus, A. cf. amplificus,. and Reticulofenestra rotaria confirms a Messinian age. The lower part of the Cozzo Salice section is rich of Gt. conomiozea, while its middle and the upper part is barren in planktonic foraminifers. In the Vallone Casino and Cozzo Sant'Isidoro sections the Tortonian-Messinian boundary corresponds to the first occurrence (FO) of Gt. miotumida group (sensu Hilgen et al., 2000), just above the first occurrence of A. delicatus. Biostratigraphic data allowed to correlate the Messinian silty layers of Amantea Basin with the coeval diatomitic beds of Rossano Basin indicating that the two areas, during the Messinian, had different paleogeographic and palaeoecological evolution.